MICROFINANCE: METHODOLOGICAL REVIEW AND RESEARCH AGENDA - Leite, Rodrigo de Oliveira (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2018)
In this article, I review evidences from several Microfinance studies. The literature shows contradictory results and sometimes fails to provide enough evidence for some effects, especially on consumption, income and empowerment of women. Nevertheless, the results provided evidence that Microfinance can help the poor to become entrepreneurs, grow their business and save more. I also discuss about different design and statistical methodologies such as cross-sectional analysis, panel data analysis, RCTs, dynamic panel data and lab experiments. I also discuss about the importance not only of a clear research design but also of statistical transparency. I also highlight a future research agenda.